GE_GERICHTE C/19147/2015 vom 23. Mai 2018 - GE Cour de justice (2018)
DIVORCE ; MODIFICATION(EN GÉNÉRAL) ; OBLIGATION D'ENTRETIEN ; ENFANT ; MAJORITÉ(ÂGE) ; DROIT À DES CONDITIONS MINIMALES D'EXISTENCE ; SUBROGATION | CC.289.al2; CC.277.al2